Heavy rainfall in the Manuel Alves da Natividade river Watershed, Tocantins, Brazil (Research, Society and Development, 2021)
The correct forecast and analysis of the spatial distribution of intense rainfall is important for the planning of water resources in hydrographic basins, in addition to supporting climatological and meteorological studies and the elaboration of projects with different and/or integrated purposes. The use of spatialization techniques, available in Geographic Information Systems, facilitates the verification of how these precipitations are distributed in space, as well as the association with different environmental factors. These techniques allow to cover large regions with agility and precision. This study is geared at mapping intense rainfall in the hydrographic basin of the Rio Manuel Alves da Natividade. The mapping of intense rains with durations of 10, 20, 30, 40, 50, 60, 120, 180, 360, 720 and 1440 minutes was made, associated with the return times of 5, 50 and 100 years. Historical series of 25 pluviometric stations were analyzed, with a standardized period between 1986 and 2016. An area with intense rain of greater magnitude was found for short durations with 10, 20, 30 and 40 minutes, considering the 3 return times, in the western portion of the Basin. For durations of 50, 60, 120 and 180 minutes, with return times of 5, 50 and 100 years, the western portion of the basin showed the highest intensities, with an emphasis on the return time of 100 years. In durations 240, 360, 720 and 1440, although the highest values ​​are found in the western portion, they do not represent great precipitation intensities, varying from 3 to 46 mm h-1.